Optimizing Outcomes Following Allogeneic Hematopoietic Progenitor Cell Transplantation in AML: The Role of Hypomethylating Agents - Martino, Massimo; Fedele, Roberta; Moscato, Tiziana; Ronco, Francesca (Current Cancer Drug Targets, 2013)
Aberrant DNA methylation is a key pathological mechanism in myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML), and provides rationale for the clinical development of hypomethylating agents (HMAs) for the treatment of these diseases. One HMA, azacitidine (Vidaza®, Celgene Corp.), has demonstrated improved survival versus conventional care regimens in patients with intermediate-2/high-risk MDS and AML (20-30% blasts) and has a favorable tolerability profile. Emerging evidence indicates that azacitidine can have an immunomodulatory effect by, for example, increasing functional regulatory T-cell (Treg) numbers and killer-cell-immunoglobulin-like receptor expression. Allogeneic hematopoietic progenitor cell transplantation (allo HPCT) is the only potentially curative treatment approach in patients with advanced MDS or AML. Unfortunately, allo HPCT in these settings is limited because most patients are ineligible due to age/comorbidities, or are at a high risk of treatment failure due to disease relapse. Recent studies have shown that azacitidine after allo HPCT increases Treg numbers while inducing a cytotoxic CD8+ T-cell response, suggesting a potential mechanism for augmenting the graft-versus-leukemia (GvL) effect without increasing graft-versushost- disease (GVHD). In patients at a high risk of relapse following allo HPCT, pre-emptive azacitidine may help prevent/delay relapse. For patients who have relapsed following allo HPCT, azacitidine may be a salvage therapy option, either as monotherapy or in combination with donor lymphocyte infusions (DLI). In this mini-review, we discuss these emerging clinical data for HMAs in the post-allo HPCT regimens and highlight the possible future role of azacitidine in this setting.
Keywords: MDS